Trainspotting - Boyle, Danny; McGregor, Ewan, 1971-; Bremner, Ewen; Miller, Jonny Lee; McKidd, Kevin; Carlyle, Robert, 1961- (PolyGram Video International, 1999)
Η ιστορία του Mark Rento και των "φίλων" του - ένα τσούρμο από αποτυχημένους, ψεύτες, ψυχοπαθείς, κλέφτες και πρεζόνια.